Gut morphology of diploid and triploid Atlantic cod, Gadus morhua. (7th May 2013) - Peruzzi, S.; Jobling, M.; Falk‐Petersen, I.‐B.; Lein, I.; Puvanendran, V.
Summary: Little is known about the functional consequences of triploidy in Atlantic cod. This study compared the gut morphology of diploid and triploid offspring of wild and selected broodstock. Three‐year‐old triploid offspring of wild cod (mean weight 1695 ± 346 g) had approximately 18% fewer pyloric caeca (125 ± 9 vs 172 ± 14, P < 0.001) and a 23% shorter intestine [Relative Gut Length, (RGL); 1.40 ± 0.17 vs 1.81 ± 0.17, P < 0.05] than their diploid siblings (mean weight: 1820 ± 262 g). Two‐year‐old triploid offspring of selected broodstock (mean weight: 640 ± 64 g) had 20% fewer pyloric caeca (309 ± 17 vs 387 ± 27, P < 0.001) but similar RGL to their diploid siblings (mean weight: 820 ± 69 g). The average number of mucus cells in the columnar epithelium of pyloric caeca was significantly higher in triploid than in diploid cod (54 ± 9 vs 25 ± 5, P < 0.001). There was no correlation between pyloric caeca number and RGL, or between mucus cells and pyloric caeca number, and no significant differences between sexes for any of the measured variables. Overall, the observations highlight some differences in the digestive system of these two ploidy groups that could have an influence on nutrient utilization and performance capacity in triploids compared to diploids.